Plan recognition scheme using multi-factors authentication for smart card online system - Mohd Ariffin, Noor Afiza; Mohd Sani, Nor Fazlida (IEEE (IEEE Xplore), 2014)
Authentication is one of the essential security features in network communication and ensures the system resources are not obtained by illegal users. In authentication process, the originator of the communication and the respondent will manage some identification codes of each other before to start of the message transaction. Several approaches have been proposed regarding the authentication process from time to time. However, the previous approaches are vulnerable to various attacks. This research introduces a new scheme named plan recognition authentication scheme that use for smart card based on networking system. It is an authentication scheme which is different with existing scheme to ensure and enhance the smart card based authentication and security. All the features of this scheme such as reliability, integrity, confidentiality and accessibility are applied during the authentication process. In this plan recognition scheme, the technique that use to identify authentication with combination of something known and something possessed such as a usage of smart card and password.